PLANNING OF RECYCLED PLASTIC MATERIAL USAGE WITH SUSTAINABLE DEVELOPMENT SYSTEM AT POLITEKNIK MANUFAKTUR ASTRA - Neilinda Novita Aisa, S.T. (Technologic, 2015)
One of many kinds of production processes in Politeknik Manufaktur Astra is Plastic Injection Process with ABS material. This process will produce plastic and scrap. The amount of plastic scrap that is produced by this process reaches 50% of all of the amount. To increase the efficiency of ABS material and build up the culture of Sustainable Development System so that is done a kind of research that is focused on the utilization of plastic waste material from Process of Plastic Injection by doing a recycle process and using the product of recycle as the basic additive material in Plastic Injection Process. To figure out the properness of the material of recycled plastic as the main material in Plastic Injection Process so is also done a tensile test to any composition of recycled ABS material and valuing certain mechanical properties that are similar to original ABS material. Moreover to cut the cost of ABS material providing so is done an analysis of material reservation with EOQ method to figure out the economic number of material reservation. The calculation of EOQ showed the most economic amount per reserving is 75kg/reserve. By the utilization of recycled material and usage of EOQ method on providing the ABS material so that Politeknik Manufaktur Astra can do a cost reduction for 36%. Key Words : Injection Process, ABS Material. Recycle, EOQ